Caracterização vegetativa e produtiva de genótipos de Coffea canephora cultivados em altitude de transição com diferentes manejos de água e solo - Jordaim, Renan Baptista (2020)
The Coffea canephora species, despite its high rusticity, has shown production losses over the last years due to high temperatures and irregular rainfall. Thus, the selection of genotypes most adapted to the different cultivation conditions has been the s